Manufacturing method of high-toughness high-chromium cast iron roller

By adding nitrogen, titanium and boron elements to high-chromium cast iron rolls, the carbide form is regulated, and the problem of excessive amounts and coarse sizes in the rolls is solved, the strength, toughness and wear resistance of the rolls are improved, and the use is extended Lifespan and reduce costs.

CN119187488APending Publication Date: 2024-12-27ZAOZHUANGXUECHENGRUIXING MASCH MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310580.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-chromium cast iron rolls have too many carbides and are large in size, resulting in low strength and toughness, which is prone to peeling and cracking on the rod wire rolling mill, affecting the normal operation of the rolling steel production line.

Method used

Add a small amount of nitrogen and appropriate amount of titanium to the high-chromium cast iron roll. By regulating the solidification and precipitation process of TiN and TiC, the refinement and distribution of M7C3 type carbides are achieved, and trace boron elements are added to improve the hardening of the roll. Hardenability and wear resistance.

Benefits of technology

It significantly improves the strength and toughness of high-chromium cast iron rolls, enhances wear resistance and thermal fatigue resistance, extends service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050568280000181
    Figure BDA0005050568280000181
  • Figure HDA0005050568420000011
    Figure HDA0005050568420000011
Patent Text Reader

Abstract

The invention discloses a high-toughness high-chromium cast iron roller manufacturing method and belongs to the technical field of rollers. The roller is formed by centrifugally compounding a high-chromium cast iron outer layer and a nodular cast iron roller core, and outer-layer high-chromium cast iron molten iron and roller core nodular cast iron molten iron are smelted respectively. The high-chromium cast iron molten iron is prepared from the following chemical components in percentage by mass: 2.47 to 2.63 percent of C, 18.65 to 18.98 percent of Cr, 0.77 to 0.94 percent of Mo, 0.58 to 0.73 percent of W, 0.67 to 0.86 percent of Si, 1.24 to 1.37 percent of Mn, 0.13 to 0.17 percent of N, 0.32 to 0.37 percent of Al and 0.35 to 0.44 percent of Ti and lt; 0.040% S, lt; 0.045% of P, and the balance Fe and inevitable impurities. The roller is subjected to centrifugal casting forming, quenching and tempering treatment, has high strength and toughness and excellent wear resistance, and is used in a slitting rack of a rod and wire rolling mill, and the service life of the roller is prolonged by 70-90% compared with that of a traditional bainite ductile iron roller.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for manufacturing a high-chromium cast iron roll, in particular to a method for manufacturing a high-strength and high-toughness high-chromium cast iron roll, and belongs to the technical field of casting. Background Art

[0002] Rollers are important consumable spare parts in steel rolling production. The performance of rolls has an important impact on the production efficiency of rolling mills and the surface quality of rolled products. With the improvement of the automation level of rolling mills and the continuous improvement of users' requirements for the dimensional accuracy and surface quality of rolled products, traditional roll materials are difficult to meet the needs of steel rolling companies. The development of new roll materials and the research on improving the service life of rolls have attracted the attention of roll science and technology workers at home and abroad. Commonly used hot rolling roll materials include semi-steel, high nickel-chromium infinitely chilled cast iron, high chromium cast iron, high chromium steel and high-speed steel.

[0003] Chinese invention patent CN115044836A discloses an improved graphite semi-steel roller and its preparation method. The chemical composition and weight percentage of the roller are: C is 1.3%-2.1%, Si is 0.4%-0.8%, Mn is 0.6%-1.6%, Cr is 0.7%-2.0%, Ni is 0%-2.0%, Mo is 0.2%-0.8%, and the rest is Fe and inevitable impurities. The matrix of the roller contains dispersed spherical graphite. The invention reduces the hardness drop of the roller and improves the wear resistance by adding an appropriate amount of silicon element and dispersed spherical graphite with self-cooling and self-lubricating ability in the matrix, so that the roller is not easy to produce fatigue cracks when processing deep hole type rolled products, thereby improving the surface quality of the product. Chinese invention patent CN110343956A also discloses a GVTi wear-resistant semi-steel roller, comprising the following components in mass percentage: C1.60-2.00, Si0.80-1.60, Mn0.60-1.20, Ni1.20-3.00, Cr0.80-2.00, Mo0.50-1.00, V0.10-0.60, Ti0.10-0.30, S≤0.03, P≤0.03, AL0.05-0.10, CaSi0.10-0.30, and the rest is Fe and unavoidable impurities. At the same time, the invention also discloses a preparation method of the above GVTi wear-resistant semi-steel roller. The invention improves the heat crack resistance of the roller by the silicon / carbon ratio, and the roller strength is further improved, with a tensile strength of ≥650Mpa; the overall casting performance is further optimized by adding a reasonable ratio of nickel, chromium, molybdenum, vanadium, and titanium alloys, especially adding vanadium and titanium alloys, which can ensure good hardness from the inside to the outside, and the roller hardness reaches 55 / 70HSD, and the wear resistance of the final roller product is improved by 20-30%. Chinese invention patent CN103614657A also discloses a method for manufacturing a high nickel-chromium alloy semi-steel roller. According to the composition requirements of the high nickel-chromium alloy semi-steel roll to be melted, the raw materials are placed in medium frequency induction electric melting, furnace pretreatment, steel casting, rough machining, quenching, tempering, and finishing. The heating rate of the quenching process is 15±5℃ / h, and the temperature is kept at 850-890℃ for 15-30h, then air-cooled or spray-cooled to 430-450℃ for 4-8 hours, and then air-cooled to 150-170℃ for discharge. The tempering process is 480-520℃ for 10-15h, and then cooled to below 100℃ with the furnace and then discharged by air cooling. The roll of the invention has high wear resistance and strong toughness, is not easy to peel off, and has good thermal crack resistance. The biggest feature is that there is almost no hardness drop in the working layer, which can greatly improve work efficiency. However, the semi-steel roll has low hardness and poor wear resistance.

[0004] Chinese invention patent CN101177759A discloses a centrifugal composite improved infinitely chilled cast iron roll and its preparation method. The chemical composition of the roll body is (weight %): 3.2-3.8C, 3.8-4.5Ni, 1.2-1.8Cr, 0.2-0.4Mo, 0.2-0.5Cu, 1.0-1.8Si, <0.8Mn, 0.10-0.30Nb, 0.05-0.20V, 0.05-0.20Ti, 0.04-0.07Mg, 0.02-0.05Y, 0.01-0.03Sb, and the rest is Fe and inevitable trace impurities. The roll of the invention can be produced by using an electric furnace and formed by a centrifugal casting method. The roll has high strength and hardness, good toughness, hardness uniformity and hardenability, excellent wear resistance and oxidation resistance, and good resistance to cold and hot shocks. It does not break, peel, crack, or stick to steel during use, and its performance is significantly better than that of high nickel-chromium infinitely cold hardened cast iron rolls. Chinese invention patent CN1598030A also discloses improvements to nickel-chromium-molybdenum infinitely cold hardened cast iron, and in particular relates to a nickel-chromium-molybdenum infinitely cold hardened cast iron for rolls with good wear resistance and heat crack resistance and long service life, characterized in that 0.03-0.1% (WT) of boron and 0.2-1.5% of niobium are added to the nickel-chromium-molybdenum infinitely cold hardened cast iron (IV) component, as well as a composite roll made of the material. Due to the addition of boron and niobium, the wear resistance and heat crack resistance of the material are significantly improved, overcoming the deficiency of the raw materials. Chinese invention patent CN101509095A also discloses ultrafine grain high nickel chromium molybdenum infinitely chilled cast iron, which is a roller material for rolling large ships. The composition weight includes: C: 2.9-3.7%, Si: 0.6-1.2%, Mn: 0.4-1.2%, Ni: 3.0 1-5.00%, Cr: 1.00-2.00%, Mo: 0.20-0.60%, and the balance Fe. There is also 1-3% antimony in the composition, which basically eliminates the network structure of carbides and makes the organization more dispersed, thereby changing the metallographic organization and properties of the material, effectively combining the wear resistance and thermal crack resistance of the material, and comprehensively improving the service life of the material. Chinese invention patent CN101851725A also discloses an alloy for improving the carbide morphology in nickel-hardened infinitely chilled cast iron. The alloy is based on the existing nickel-hardened infinitely chilled cast iron composition, and 3-6% vanadium is added by mass. The melting and casting process are properly controlled to obtain a cast iron mainly composed of uniform spherical carbides. The invention uses the VC+γ eutectic zone formed during the solidification process of high-vanadium cast iron to form fine granular carbides, and the core effect of VC on the nucleation of eutectic carbides weakens or eliminates the eutectic network carbides, and obtains a uniformly distributed organization mainly composed of granular carbides. The cast iron produced can significantly improve the wear resistance of infinitely chilled cast iron. However, the carbides in the nickel-chromium infinitely chilled cast iron roll are of M3C type, with low hardness and continuous network distribution, resulting in low strength and toughness of the roll.Although adding more vanadium and antimony elements is beneficial to improving the carbide morphology, vanadium and antimony elements are expensive and will significantly increase the cost of the roll.

[0005] Chinese invention patent CN108060365A discloses a high chromium cast steel roll for hot strip rolling, including a roll core and a roll body working layer, the chemical composition and mass percentage of the roll body working layer are C1.60-2.00%, Si0.60-1.00%, Mn0.80-1.50%, Cr12.00-15.00%, Ni1.00-2.00%, Mo1.00-2.50%, V≥0.10%, S≤0.03%, P≤0.05%, and the rest are Fe and unavoidable impurities. The invention improves the carbon content and inhibits the formation of pearlite in the cast structure by improving the chemical composition of the roll body working layer and adjusting the heat treatment process, so that the mechanical strength and wear resistance of the roll are improved, and high temperature quenching is not required during the rolling process, which can save equipment, shorten the production cycle, reduce production costs, and improve the stability of the roll performance. Chinese invention patent CN117127093A also discloses a method for manufacturing a high-chromium steel roll assembled with a combined shaft ring, which relates to the technical field of roll manufacturing. The method comprises a shaft ring and a roll made of high-chromium steel, wherein the chemical composition of the high-chromium steel is: C1.2-1.5%, Si0.4-0.8%, Mn0.4-1.1%, Cr8-13%, Ni0.3-1.0%, Mo1.0-2.5%, V0.2-0.7%, W0.2-0 .5. Its manufacturing method includes the following steps: high chromium steel roller sleeve casting; hot unpacking, cleaning, diffusion spheroidizing annealing of high chromium steel roller sleeve; rough machining, quenching and tempering of high chromium steel sleeve and fine machining and roller shaft and locking ring preparation; hot assembly of shaft ring; installation of locking ring and finishing of shape to finished product; This manufacturing method adopts sand mold with hole casting, first adjusts the roll structure through heat treatment, and then adopts special heat treatment technology of rough opening, quenching and tempering to reduce the risk of heat treatment manufacturing, and makes the roll meet the use requirements through hot assembly of shaft ring and mechanical locking.Chinese invention patent CN114850220A also discloses a high-chromium steel rolling roller with high wear resistance, comprising a main body roller (4), characterized in that a protective component (5) is arranged on one side outer wall of the main body roller (4), and heat-conducting needles (12) distributed at equal distances are fixed to the top inner wall of the main body roller (4) by screws, the heat-conducting needles (12) are made of nickel-copper alloy, and the heat-conducting needles (12) are of different lengths, a core (6) is arranged inside the main body roller (4), and the core (6) is located at the center of the main body roller (4), and the outer wall of one side of the main body roller (4) is connected to the main body roller (4) by a flange. A water injection pipe (13) is connected, and a sealing valve (14) is arranged on the outer wall of one side of the water injection pipe (13). The main body roller (4) is made of the following components in mass percentage: C: 1-1.4%, Si: 0.3-0.4%, Mn: 0.9-1.0%, P≤0.03%, S≤0.01%, Cr: 14-16%, Ni: 0.5-1.7%, Mo: 1.2-1.4%, V: 0.3-0.4%, Nb: 0.05-0.1%, RE: 0.8-1.2%, and the remainder is Fe and unavoidable impurities; the material of the core (6) is ductile iron. Chinese invention patent CN108411193A discloses a method for manufacturing a high chromium steel roll. The high chromium steel roll of the invention comprises a roll body consisting of a working layer and a core. The working layer is made of the following components in mass percentage: C: 1.25-1.35%, Si: 0.5-0.6%, Mn: 0.9-1.0%, P≤0.05%, S≤0.02%, Cr: 12-13%, Ni: 0.8-1.0%, Mo: 1.4-1.5%, V: 0.3-0.4%, Nb: 0.05-0.15%, RE: 0.5-1.0%, and the balance is Fe and unavoidable impurities; the core is made of ductile iron. However, the high chromium cast steel roll has a small amount of carbides and poor wear resistance.

[0006] Chinese invention patent CN111101062A discloses a hot-rolled improved centrifugal composite casting high-Nb high-speed steel roll, comprising the following components by mass percentage: 1.50-1.70% C, 1.40-1.60% Si, 0.60-1.00% Mn, 1.00-1.50% Ni, 5.00-8.00% Cr, 3.00-5.00% Mo, 1.00-3.00% W, 4.00-6.00% Nb, 1.00-2.00% V, ≤0.03% S, ≤0.03% P, and the rest is Fe and unavoidable impurities. At the same time, the invention also discloses a preparation method of the above-mentioned high-Nb high-speed steel roll. This invention replaces the long-lasting high-chromium steel rolls for hot rolling roughing working rolls, breaking the composition limitations of traditional centrifugal composite high-speed steel. This product can cover all working rolls on the current hot rolling mill frame, and can also be used on rod and wire rolls, and ensures the consistency of wear resistance of the entire roll. Chinese invention patent CN113621877A also discloses a centrifugal composite high-speed steel roller for a rod and wire rolling mill, characterized in that: the centrifugal composite high-speed steel roller for the rod and wire rolling mill is formed by centrifugal composite casting of an outer layer, a primary core, and a secondary core; the chemical composition and weight percentage of the outer layer are: C: 1.8-2.0%, Si: 0.65-0.75%, Mn: 0.35-0.45%, P≤0.05%, S≤0.03%, Cr: 4.4-4.6%, Ni: 0.5-0.7%, Mo: 5.9-6.1%, V: 5.9-6.1%, and the rest are iron and unavoidable impurity elements; the chemical composition and weight percentage of the primary core are: C: 1.0-1 .1%, Si: 1.5-1.6%, Mn: 0.4-0.5%, P≤0.05%, S≤0.03%, Cr≤0.2%, Ni≤0.2%, Mo≤0.2%, the rest are iron and inevitable impurity elements; the chemical composition and weight percentage of the secondary core are: C: 3.3-3.4%, Si: 2.1-2.4%, Mn: 0.4-0.5%, P≤0.08%, S≤0.015%, Cr: 0.1-0.2%, Ni: 0.4-0.5%, Mo≤0.1%, V≤0.05%, W≤0.05%, Mg: 0.03-0.06%, Re0.01-0.03%, the rest are iron and inevitable impurity elements. Chinese invention patent CN111945053A also discloses a method for preparing a high-speed steel roller subjected to composite modification.The high-speed steel roll material is melted in a medium-frequency induction furnace, and the chemical composition and mass fraction of the molten steel in the furnace are controlled at 2.32-2.49% C, 4.17-4.33% W, 4.80-4.98% Mo, 9.63-9.85% Cr, 0.48-0.66% Mn, 0.57-0.81% Si, ≤0.035% S, ≤0.040% P, and the balance is Fe; then the molten steel is heated to 1615-1626°C, aluminum is added after being kept warm for 4-5 minutes, and then the molten steel is modified by a wire feeding method, and the molten steel is poured into a high-speed rotating mold on a centrifuge. After the high-speed steel solidifies, the core is filled with ductile iron in a static state, and a high-speed steel roll with excellent performance and good use effect can be obtained after quenching and tempering. Chinese invention patent CN110387506A also discloses a high wear-resistant centrifugal composite high-speed steel roller, the chemical composition and mass percentage are: outer layer: C1.6~1.9, Si0.30~0.80, Mn0.60~1.2, P≤0.035, S≤0.030, Cr3.50~6.50, Ni0.20~1.0, Mo3.0~6.0, V2.0~6.0 ,W2.0~6.0,Nb0.5~2.0,the rest are iron and impurities;intermediate layer and core:C2.95~3.4,Si2.0~3.0,Mn0.4~1.0,P≤0.05,S≤0.035,Re0.01~0.04,Mg0.03~0.08,Cr≤0.15,Ni≤0.5,Mo≤0.1,Cu≤0.1,the rest are iron and impurities. The invention has the characteristics of high hardness,high wear resistance,high heat strength and high red hardness. Although high-speed steel rollers have good toughness,high hardness and good wear resistance, they contain more expensive alloy elements such as molybdenum,vanadium,niobium,tungsten, etc., with high production costs and poor market competitiveness.

[0007] Chinese invention patent CN115647060A discloses a high chromium cast iron roll and a production method thereof. The high chromium cast iron roll comprises a core layer, an intermediate layer and a working layer arranged in sequence from the inside to the outside, the material of the core layer is ductile iron, the material of the intermediate layer is composed of the following components in mass percentage: C 1.1%-1.3%, Si 1%-2%, Cr 2.5%-4%, Mn 0.1%-0.3%, Mo 1.6%-2.5%, the balance is Fe and inevitable impurities, the material of the working layer is high chromium cast iron, and the high chromium cast iron is composed of the following components in mass percentage: C 2.5%-2.9%, Si 0.3%-0.8%, Cr 12%-22%, Mn 0.7%-1.4%, Mo 0.8%-1.5%, Ni1.0%-1.5%, the balance is Fe and inevitable impurities. The production method of the high chromium cast iron roll comprises the following steps S1, smelting; S2, three-layer composite casting; S3, heat treatment. The above technical scheme solves the problem of low overall strength of the high chromium cast iron roll produced by the composite casting process in the prior art. Chinese invention patent CN112605388A also discloses a method for preparing a high chromium cast iron alloy composite roll, comprising the following steps: S1, preparing a high chromium cast iron alloy powder, the high chromium cast iron alloy powder comprising: C is 3.0% to 3.8%, Si is 0.5% to 1.2%, Mn is 0.3% to 0.8%, Cr is 18.0% to 28.0%, Mo is 1.0% to 3.0%, V is 2.0% to 9.0%, W is 0.2% to 2.0%, and the remainder is Fe, and the ratio of Cr to C is greater than or equal to 3.5; S2, use low carbon steel to prepare the sleeve; S3, fill the cavity in the sleeve with high chromium cast iron alloy powder; S4, evacuate the sleeve with high chromium cast iron alloy powder; S5, use electron beam welding to seal the sleeve after gas extraction; S6, hot isostatic pressing the sealed sleeve to form a composite roller sleeve semi-finished product; S7, heat treat the composite roller sleeve semi-finished product; S8, use turning to remove the sleeve on the outer surface of the composite roller sleeve semi-finished product to expose the high chromium cast iron alloy layer to obtain the composite roller sleeve; S9, assemble the composite roller sleeve with the roller shaft. The preparation method of the high chromium cast iron alloy composite roller of the invention, the outer layer of the composite roller sleeve is a high chromium cast iron alloy with high wear resistance and high red hardness, and the inner layer is a low carbon steel with good toughness, which is hard on the outside and tough on the inside, which is conducive to improving the wear resistance and safety of the composite roller sleeve.Chinese invention patent CN111394645A also discloses a high chromium cast iron roll and its preparation method, wherein the high chromium cast iron roll comprises a core, an intermediate layer and a working layer arranged in sequence from the inside to the outside, and the alloy components of the working layer are calculated by mass percentage as follows: C: 2.5-3.3%, Si: 0.6-1.0%, Mn: 0.8-1.5%, Cr: 12-18%, Ni: 1.0-2.0%, Mo: 1.0-2.0%, V: 1.0-2.0%, P: <0.05%, S: <0.05%, and the rest are Fe and unavoidable impurities. The working layer of the high chromium cast iron roll described in the invention can have a higher hardness, can improve the quality of rolled materials, and reduce roll consumption. Chinese invention patent CN109261925A also discloses a high chromium cast iron roll, comprising a high chromium cast iron working layer and a ductile iron roll core, the chemical composition of the working layer and its mass percentage are: C: 2.1-2.9%, Si: 0.4-0.8%, Mn: 0.5-0.8%, Cr: 15-20%, Ni: 0.5-2%, Mo: 0.5-2%, V: 0-0.4%, Cu: 0.2-0.8%, RE: 0.01-0.03%, P: ≤0.15%, S: ≤0.15%, and the balance is iron. The composite centrifugal casting method is adopted in the preparation. The molded roll obtained by casting is demolded when the surface temperature of its working layer is 800-850℃, air-cooled to 200℃-300℃, then kept warm for 5-10h, and then heated to 950-980℃ at a rate of 9-12℃ / h, kept warm for 30-60min, quenched, and then heated to 280-300℃ for tempering, kept warm for 8-10h, and high chromium cast iron roll is obtained. However, there are too many carbides in ordinary high chromium cast iron rolls, and the carbides are coarse in size, resulting in low strength and toughness of the rolls. When used on the slitting rack of the rod and wire mill, ordinary high chromium cast iron rolls are prone to peeling and cracking, which seriously affects the normal operation of the steel rolling production line. Summary of the invention

[0008] The semi-steel rolls have low hardness and poor wear resistance. The carbides in the nickel-chromium infinitely chilled cast iron rolls are of M3C type, with low hardness and continuous network distribution, resulting in low roll strength and toughness. The high-chromium cast steel rolls have a small number of carbides and poor wear resistance. The high-speed steel rolls contain more expensive alloy elements such as vanadium, niobium, and cobalt, with high production costs and poor market competitiveness. In addition, the ordinary high-chromium cast iron rolls have too many carbides and large carbides, resulting in low roll strength and toughness. The ordinary high chromium cast iron roll is prone to peeling and cracking when used on a sub-frame, which seriously affects the normal operation of the steel rolling production line. The present invention proposes to add a small amount of nitrogen and an appropriate amount of titanium element to the high chromium cast iron roll, and achieve the refinement and uniform distribution of M7C3 type carbides by regulating the solidification and precipitation process of TiN and TiC, thereby improving the strength and toughness of the high chromium cast iron roll. On this basis, a trace amount of boron element is added to further improve the hardenability, hardenability and wear resistance of the high chromium cast iron roll.

[0009] A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll, characterized in that the high-strength and high-chromium cast iron roll is centrifugally compounded by a high-chromium cast iron outer layer and a ductile iron roll core, and the specific preparation process steps are:

[0010] ① Two acidic medium frequency induction furnaces are used to melt the outer layer high chromium cast iron and the roller core ductile iron respectively; the smelting process of high chromium cast iron is: first add scrap steel and carburizer into the acidic medium frequency induction furnace, and then add ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese to adjust the composition of the molten iron after the molten iron is melted; then heat the molten iron to 1566-1579℃, add metal aluminum and ferrotitanium in turn, and control the chemical composition and mass fraction of the molten iron in the furnace to 2.47 -2.63% C, 18.65-18.98% Cr, 0.77-0.94% Mo, 0.58-0.73% W, 0.67-0.86% Si, 1.24-1.37% Mn, 0.13-0.17% N, 0.32-0.37% Al, 0.35-0.44% Ti, <0.040% S, <0.045% P, the rest is Fe and unavoidable impurities; when the temperature of the molten iron in the furnace drops to 15 At 17-1532℃, the molten iron is discharged from the furnace to the ladle, and during the molten iron discharge process, titanium iron particles and ferroboron particles preheated at 850-900℃ for 120-150 minutes are added with the molten iron flow, the amount of titanium iron particles added accounts for 1.2-1.4% of the mass fraction of the molten iron entering the ladle, and the amount of ferroboron particles added accounts for 0.35-0.37% of the mass fraction of the molten iron entering the ladle. The size of the titanium iron particles and ferroboron particles is 2-4mm; The copper-magnesium alloy and the rare earth ferrosilicon alloy are added in an amount of 0.35-0.38% and 0.10-12% of the mass fraction of the molten iron added to the ladle, respectively, and the size of the copper-magnesium alloy and the rare earth ferrosilicon alloy is 5-8 mm; after all the molten iron enters the ladle, a proper amount of heat-insulating slag-aggregating agent is sprinkled into the ladle to cover it, and the slag is removed after calming for 4-5 minutes to obtain high-chromium cast iron molten iron, and when the temperature drops to 1426-1433°C, it is poured into a casting mold on a centrifuge;

[0011] ② The smelting process of roller core ductile iron molten iron is to first mix and heat the waste cast iron, waste ductile iron, scrap steel and carburizer in another acidic medium frequency induction furnace to melt, add metallic copper after the molten iron is melted, heat the molten iron to above 1450℃, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.13-3.38% C, 0.91-1.07% Si, 0.41-0.48% Cu, 0.05-0.09% Ti, 0.32-0.49% Mn, <0.25% Cr, ≤0.20% Ni, ≤0.20% Mo, ≤0.070% P, ≤0.035% S, the rest is Fe and unavoidable impurities; the temperature of the molten iron out of the furnace is controlled at 1482-1497°C, and in the process of the molten iron out of the furnace, ferrosilicon particles preheated at 650-720°C for 90-110 minutes are added with the molten iron flow, the amount of ferrosilicon particles added accounts for 0.7-0.8% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15mm; rare earth magnesium ferrosilicon alloy is pre-added at the bottom of the ladle, the amount of rare earth magnesium ferrosilicon alloy added accounts for 1.40-1.50% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; the molten iron in the ladle is skimmed and allowed to stand to obtain ductile iron molten iron, and when the temperature drops to 1318-1327°C, it is poured into the mold on the centrifuge;

[0012] ③ The high chromium cast iron molten iron of 1426-1433° C. obtained in step ① is poured into a casting mold rotating at high speed on a vertical centrifuge, and the centrifuge speed is 950-1050rpm; the thickness of the outer layer of the high chromium cast iron is 40-60mm; after the outer layer molten iron is poured, "O" type glass slag dried at 150-180° C. for 2.0-2.5 hours is added, and the amount of "O" type glass slag is added according to the inner surface area of ​​the outer layer of the high chromium cast iron per square meter (i.e., 1.1-1.2kg / m 2 ) meter; when the outer layer of molten iron is poured for 6-8 minutes, the centrifuge speed is reduced to 750-800rpm; the inner surface temperature of the outer layer is measured with a far-infrared thermometer. When the inner surface temperature is 1280-1300°C, the mold speed is reduced to 600-650rpm, and the ductile iron molten iron of 1318-1327°C obtained in step ② is poured; 28-32 minutes after the ductile iron molten iron is poured, the centrifuge is stopped; after continuing to cool in the mold for 3-4 hours, the roller is removed from the mold;

[0013] ④ The rollers are roughly processed after grinding and sand cleaning. The rough-processed rollers are heated to 980-1010℃ with the furnace, kept warm for 3-3.5 hours, spray-cooled to the roller surface temperature of 380-450℃ after being taken out of the furnace, and then heated to 530-560℃ in the furnace, kept warm for 12-14 hours, cooled in the furnace to a temperature below 160℃, air-cooled to room temperature after being taken out of the furnace, and finally fine-processed to the specified size and precision to obtain high-strength and high-toughness high-chromium cast iron rollers.

[0014] As mentioned above, the chemical composition and mass fraction of the titanium-iron particles are: 68.64-71.28% Ti, <0.5% Al, <0.10% Si, <0.20% Mn, <0.20% C, <0.03% P, <0.03% S, <0.50% V, and the remainder is Fe and unavoidable impurities.

[0015] As mentioned above, the chemical composition and mass fraction of the ferroboron particles are: 19.54-20.76% B, ≤0.5% C, ≤2% Si, ≤0.5% Al, ≤0.01% S, ≤0.1% P, and the remainder is Fe and unavoidable impurities.

[0016] As mentioned above, the chemical composition and mass fraction of the copper-magnesium alloy are: 94-95% Cu, 5-6% Mg, and the sum of the two is 100%.

[0017] As mentioned above, the chemical composition and mass fraction of rare earth ferrosilicon alloy are: 36.45-37.81% RE, 44.06-46.50% Si, <2.0% Ba, <2.0% Ca, <1.5% Al, <0.3% Ti, <0.5% Mn, and the remainder is Fe and unavoidable impurities.

[0018] As mentioned above, the chemical composition and mass fraction of the ferrosilicon particles are: 74.82-76.17% Si, ≤1.0% Al, ≤1.0% Ca, ≤0.5% Mn, ≤0.5% Cr, ≤0.04% P, ≤0.02% S, ≤0.20% C, and the remainder is Fe and unavoidable impurities.

[0019] As mentioned above, the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 6.36-7.81% RE, 7.24-8.68% Mg, 38.17-42.05% Si, ≤1% Ti, ≤1% Al, and the remainder is Fe and unavoidable impurities.

[0020] The present invention mainly ensures that the roller has high wear resistance and excellent toughness, and ensures that the roller is used on the slitting frame of the rod and wire mill without cracking or peeling. The present invention proposes to use high chromium cast iron to manufacture rollers based on the analysis that semi-steel rollers have low hardness and poor wear resistance, the carbides in nickel-chromium infinitely chilled cast iron rollers are M3C type, with low hardness and continuous network distribution, resulting in low strength and toughness of the rollers, the carbides in high chromium cast steel rollers are small in number and poor in wear resistance, and the high-speed steel rollers contain more expensive alloy elements such as vanadium, niobium, and cobalt, with high production costs and poor market competitiveness. The eutectic carbide of high chromium white cast iron with Cr content greater than 12% is hexagonal (Cr,Fe)7C3 (abbreviated as M7C3), and its microhardness is 1400-1800HV, which is higher than the eutectic carbide Fe3C (840-1100HV) of ordinary white cast iron. At the same time, the solidification characteristics change. During solidification, (Cr,Fe)7C3 is an isolated phase, while austenite is a continuous phase. Therefore, the toughness is greatly improved compared with ordinary white cast iron. Therefore, it is the preferred material for abrasive wear and cutting wear resistance. It is mainly used for large and medium-sized wear parts such as liners, hammers, grinding balls, slurry pump flow parts under medium and low impact load conditions. It is also used as the roller of the plate and strip mill, showing excellent use effect. Ordinary high-chromium cast iron rolls contain too many carbides and their sizes are large, resulting in low roll strength and toughness. When used on the slitting rack of a rod and wire mill, ordinary high-chromium cast iron rolls are prone to peeling and cracking, which seriously affects the normal operation of the steel rolling production line. The present invention proposes to add a small amount of nitrogen and an appropriate amount of titanium to the high-chromium cast iron roll, and to achieve the refinement and uniform distribution of M7C3 type carbides by regulating the solidification and precipitation processes of TiN and TiC, thereby improving the strength and toughness of the high-chromium cast iron roll. On this basis, a trace amount of boron is added to further improve the hardenability, hardenability and wear resistance of the high-chromium cast iron roll. The high-strength and toughness high-chromium cast iron roll is centrifugally compounded by a high-chromium cast iron outer layer and a ductile iron roll core. The specific preparation process steps are:

[0021] The present invention uses two acidic medium frequency induction furnaces to melt the outer layer high chromium cast iron molten iron and the roller core ductile cast iron molten iron respectively. The medium frequency induction furnace is used to melt the molten iron, and the operation process is simple and the cast iron composition is easy to adjust. In addition, the acidic furnace lining is low in price and is suitable for melting high chromium cast iron molten iron and ductile cast iron molten iron. The smelting process of high chromium cast iron molten iron is: firstly add scrap steel and carburizer into the acidic medium frequency induction furnace, and then add ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese to adjust the composition of the molten iron after the molten iron is melted; then heat the molten iron to 1566-1579℃, add metallic aluminum and ferrotitanium in turn, and control the chemical composition and mass fraction of the molten iron in the furnace to 2.47-2.63%C, 18.65-18.98%Cr, 0.77-0.94%Mo, 0.58-0.73%W, 0.67-0.86%Si, 1.24-1.37%Mn, 0.13-0.17%N, 0.32-0.37%Al, 0.35-0.44%Ti, <0.040%S, <0.045%P, and the rest is Fe and unavoidable impurities. The high chromium cast iron of the present invention belongs to a hypoeutectic composition, and the primary phase is an austenite phase. The main functions of carbon and chromium are to ensure the quantity and morphology of carbides in cast iron. As the C content increases, the carbides increase; as the Cr / C ratio increases, the morphology of eutectic carbides undergoes a process of continuous network, lamellar, and rod-shaped continuous degree reduction, and the eutectic carbide lattice type undergoes a change process from M3C→M3C+M7C3→M7C3. When the eutectic carbides remain unchanged and the chromium-carbon ratio (Cr / C) is greater than 7, the fracture toughness and tensile strength of the high chromium cast iron are significantly improved, that is, the crack propagation resistance is the strongest at this time. According to these principles, the mass fraction of C in the present invention is set to 2.47-2.63%C, and the mass fraction of Cr is set to 18.65-18.98%. Cr in the matrix can also improve the hardenability of the material. The chromium-carbon ratio (Cr / C) of the present invention is high, greater than 7, ensuring that the carbides in the high chromium cast iron are M7C3 type carbides with high hardness and high fracture toughness. The high chromium cast iron of the present invention contains 0.13-0.17% N and 0.35-0.44% Ti, and fine high-melting-point TiN particles can be precipitated at high temperatures. The high-melting-point TiN particles can serve as primary austenite crystallization cores and TiC crystallization cores, promoting the refinement of primary austenite and the refinement of TiC.

[0022] In the present invention, when the temperature of the molten iron in the furnace drops to 1517-1532°C, a large number of fine high-melting-point TiN particles have been precipitated. At this time, the molten iron is discharged from the furnace to a ladle, and during the molten iron discharge process, titanium iron particles preheated at 850-900°C for 120-150 minutes are added with the molten iron flow (the chemical composition and mass fraction of the titanium iron particles are: 68.64-71.28% Ti, <0.5% Al, <0.10% Si, <0.20% Mn, <0.20% C, <0.03% P, <0.03% S, <0.50% V, the balance is Fe and inevitable impurities) and ferroboron particles (the chemical composition and mass fraction of the ferroboron particles are: 19.54-20.76% B, ≤0.5% C, ≤2% Si, ≤0.5% Al, ≤0.01% S, ≤0.1% P, the balance is Fe and inevitable impurities), the amount of ferrotitanium particles added accounts for 1.2-1.4% of the mass fraction of the molten iron entering the ladle, the amount of ferroboron particles added accounts for 0.35-0.37% of the mass fraction of the molten iron entering the ladle, and the size of the ferrotitanium particles and ferroboron particles is 2-4mm. The addition of ferrotitanium particles is mainly to promote the formation of a large number of high-hardness fine TiC particles in high-chromium cast iron with high melting point TiN particles as the solidification core, which are distributed in the high-chromium cast iron to improve the hardness and wear resistance of the high-chromium cast iron. The addition of ferroboron particles utilizes the boron element to solid-dissolve in the high-chromium cast iron matrix, improves the hardenability and hardenability of the matrix, and promotes a significant improvement in the wear resistance of the high-chromium cast iron. Adding 0.32-0.37% Al, 0.77-0.94% Mo and 0.58-0.73% W can improve the tempering stability and high-temperature wear resistance of high-chromium cast iron. Aluminum has a strong deoxidation effect and is easy to react with oxygen and nitrogen in molten iron to form high-melting point aluminum oxide and aluminum nitride, which are dispersed in the molten iron to form a large number of crystal cores. Since austenite precipitates first, it not only refines the austenite grains, but also prevents the subsequent eutectic carbide from growing and continuing. All of this creates conditions for improving the toughness of cast iron.

[0023] The present invention also pre-adds copper-magnesium alloy (the chemical composition and mass fraction of the copper-magnesium alloy are: 94-95% Cu, 5-6% Mg) and rare earth ferrosilicon alloy (the chemical composition and mass fraction of the rare earth ferrosilicon alloy are: 36.45-37.81% RE, 44.06-46.50% Si, <2.0% Ba, <2.0% Ca, <1.5% Al, <0.3% Ti, <0.5% Mn, the remainder is Fe and inevitable impurities) at the bottom of the ladle, the added amounts of the copper-magnesium alloy and the rare earth ferrosilicon alloy account for 0.35-0.38% and 0.10-12% of the mass fraction of the molten iron added to the ladle respectively, and the sizes of the copper-magnesium alloy and the rare earth ferrosilicon alloy are 5-8mm. After all the molten iron enters the ladle, sprinkle an appropriate amount of heat-insulating slag-aggregating agent into the ladle to cover it, and then stagnate it for 4-5 minutes before skimming off the slag to obtain high-chromium cast iron molten iron. When the temperature drops to 1426-1433℃, pour it into the mold on the centrifuge. The characteristics of rare earth elements are low melting point and large atomic radius. They are strongly supercooled elements in high-chromium cast iron and are also non-carbide forming elements. Therefore, during the solidification process, they will be enriched in the melt at the front of the primary austenite crystallization through solute redistribution, causing the composition to be supercooled and the primary austenite dendrite to be refined. Rare earth elements are adsorbed on the growing eutectic carbides, which increases the eutectic supercooling and the eutectic solidification range, resulting in a large number of nuclei for the eutectic carbides. The rare earth elements segregated in the melt at the front of the growth direction of the eutectic carbide prevent the iron, chromium and carbon atoms in the melt from entering the eutectic carbide crystals normally, reducing the growth rate of the eutectic leading phase carbide in the preferred growth direction, resulting in the dispersion of carbides, thereby promoting the uniform distribution of carbides. It is precisely because of the improvement of carbide morphology that the crack propagation path is hindered during brittle fracture, thereby improving the impact toughness and tensile strength of high chromium cast iron.

[0024] The roll core of the roll of the present invention is made of high-strength and toughness ductile iron. The smelting process of the ductile iron molten iron of the roll core is to first mix and heat the waste cast iron, waste ductile iron, waste steel and a carburizer in another acidic medium-frequency induction furnace to melt, add metal copper after the molten iron is melted, heat the molten iron to above 1450°C, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.13-3.38% C, 0.91-1.07% Si, 0.41-0.48% Cu, 0.05-0.09% Ti, 0.32-0.49% Mn, <0.25% Cr, ≤0.20% Ni, ≤0.20% Mo, ≤0.070% P, ≤0.035% S, and the rest is Fe and inevitable impurities. The ductile iron of the present invention contains 0.41-0.48% Cu, which can improve the strength of the ductile iron. Adding 0.05-0.09% Ti can significantly refine the solidification structure of ductile iron and improve its strength and toughness. Elements such as chromium, nickel, and molybdenum are brought in from waste cast iron, waste ductile iron, and waste steel. The amount of chromium brought in must be strictly controlled. In particular, a large amount of chromium will deteriorate the shape of graphite and damage the mechanical properties of ductile iron. The temperature of the molten iron out of the furnace is controlled at 1482-1497° C., and in the process of the molten iron out of the furnace, ferrosilicon particles (the chemical composition and mass fraction of the ferrosilicon particles are: 74.82-76.17% Si, ≤1.0% Al, ≤1.0% Ca, ≤0.5% Mn, ≤0.5% Cr, ≤0.04% P, ≤0.02% S, ≤0.20% C, and the balance is Fe and inevitable impurities) are added along with the molten iron flow. The amount of ferrosilicon particles added accounts for 0.7-0.8% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15 mm. The ferrosilicon particles mainly play a role in inoculation, which is conducive to the refinement of the size of the graphite balls. The present invention also adds rare earth magnesium ferrosilicon alloy in advance at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 6.36-7.81% RE, 7.24-8.68% Mg, 38.17-42.05% Si, ≤1% Ti, ≤1% Al, the balance is Fe and inevitable impurities), and the use of rare earth magnesium ferrosilicon alloy spheroidizing agent can improve the ability to resist graphite spheroidization decline. The amount of rare earth magnesium ferrosilicon alloy added accounts for 1.40-1.50% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; the molten iron in the ladle is skimmed and left to stand to obtain ductile iron molten iron, and when the temperature drops to 1318-1327°C, it is poured into the casting mold on the centrifuge;

[0025] The invention further pours the high chromium cast iron molten iron with a temperature of 1426-1433° C. obtained by smelting into a high-speed rotating mold on a vertical centrifuge, and the centrifuge speed is 950-1050 rpm; the thickness of the outer layer of the high chromium cast iron is 40-60 mm; after the outer layer of molten iron is poured, "O" type glass slag dried at 150-180° C. for 2.0-2.5 hours is added, and the amount of "O" type glass slag is 1.1-1.2 kg (1.1-1.2 kg / m2) per square meter of the inner surface area of ​​the outer layer of the high chromium cast iron. 2 ) meter. Adding "O" type glass slag can prevent the oxidation of molten iron, improve the metallurgical bonding effect of the outer layer high chromium cast iron and the roller core ductile iron, and increase the strength of the bonding layer. After the outer layer of molten iron has been poured for 6-8 minutes, the centrifuge speed is reduced to 750-800rpm. The inner surface temperature of the outer layer is measured with a far-infrared thermometer. When the inner surface temperature is 1280-1300°C, the mold speed is reduced to 600-650rpm, and the previously obtained ductile iron molten iron with a temperature of 1318-1327°C is poured. The present invention pours the roller core ductile iron molten iron under centrifugal rotation, which can achieve good metallurgical bonding between the outer layer and the roller core, and the thickness of the transition layer can be controlled within 5-8mm, ensuring that the rollers are firmly bonded and the chromium content of the roller core is low. It is ensured that the roller core ductile iron has high strength and high toughness. 28-32 minutes after the ductile iron molten iron is poured, the centrifuge is shut down; after cooling in the mold for 3-4 hours, the roller is taken out from the mold.

[0026] The roller of the present invention is subjected to rough processing after grinding and sand removal. The rough processed roller is heated to 980-1010°C in the furnace, kept warm for 3-3.5 hours, and spray-cooled to a roller surface temperature of 380-450°C after being taken out of the furnace. Spray cooling refers to the online controlled cooling of the roller surface by atomizing water into a mist flow with air having a certain pressure. Its cooling rate is higher than air cooling and lower than water cooling, ensuring that the roller obtains a high-hardness martensitic matrix after quenching, and has good wear resistance. The present invention continues to heat to 530-560°C in the furnace, keeps warm for 12-14 hours, cools the furnace to a temperature below 160°C, takes out of the furnace and air-cools to room temperature, and finally fine-processes to a specified size and precision, thereby obtaining a high-strength and high-chromium cast iron roller.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) The present invention effectively improves the mechanical properties of the roller by adjusting the composition ratio of the roller and adopting a composite layer structure. The hardness of the outer layer of the roller is greater than 82HSD, the tensile strength is greater than 830MPa, and the impact toughness is greater than 10J / cm 2 , the tensile strength of the roller core is greater than 650MPa and the elongation is greater than 8%.

[0029] (2) The high-chromium cast iron outer layer of the roller of the present invention and the ductile iron in the roller core achieve good metallurgical bonding, and the thickness of the transition layer formed between the high-chromium cast iron outer layer and the ductile iron in the roller core can be controlled within 5-8 mm, ensuring that the rollers are firmly bonded; the chromium content in the roller core is low, ensuring that the ductile iron in the roller core has high strength and high toughness.

[0030] (3) The roll of the present invention has high hardness, good hardness uniformity, excellent wear resistance and good thermal fatigue resistance. When used in the slitting rack of a rod and wire rolling mill, its service life is increased by 70-90% compared with that of a traditional bainitic ductile iron roll, and its production cost is reduced by more than 20% compared with that of a traditional bainitic ductile iron roll.

[0031] (4) The high chromium cast iron roll of the present invention can improve the strength, toughness and wear resistance of the roll, increase its service life, and reduce the cost of the roll. The use of the roll of the present invention can significantly improve the operation rate of the steel rolling mill, reduce the labor intensity of workers, reduce the production cost of rolled materials, and improve the surface quality of rolled materials. The promotion and application of the roll has good economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of high-strength and high-toughness high-chromium cast iron roll;

[0033] 1-High chromium cast iron outer layer, 2-Roller core ductile iron. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the embodiments, but the present invention is not limited to the following embodiments.

[0035] Embodiment 1:

[0036] The high-strength and high-toughness high-chromium cast iron roll is made of a high-chromium cast iron outer layer 1 and a ductile iron roll core 2 by centrifugal composite casting. The specific preparation process steps are:

[0037] ① Two acidic medium frequency induction furnaces are used to melt the outer layer high chromium cast iron 1 and the roller core ductile iron 2 respectively; the smelting process of the high chromium cast iron is: firstly, scrap steel and carburizer are added to a 500 kg acidic medium frequency induction furnace, and after the molten iron is melted, ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese are added to adjust the composition of the molten iron; then, the molten iron is heated to 1572°C, metallic aluminum and ferrotitanium are added in turn, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at 2.58% C, 18.84% Cr, 0.85% Mo, 0.66% W, 0.71% Si, 1.32% Mn, 0.15% N, 0.3 6% Al, 0.39% Ti, 0.028% S, 0.041% P, and the rest is Fe and inevitable impurities; when the temperature of the molten iron in the furnace drops to 1523°C, the molten iron is discharged from the furnace to a ladle, and in the process of the molten iron being discharged from the furnace, titanium iron particles (the chemical composition and mass fraction of the titanium iron particles are: 70.67% Ti, 0.38% Al, 0.04% Si, 0.08% Mn, 0.09% C, 0.025% P, 0.029% S, 0.18% V, and the rest is Fe and inevitable impurities) and ferroboron particles (the chemical composition and mass fraction of the ferroboron particles are: 70.67% Ti, 0.38% Al, 0.04% Si, 0.08% Mn, 0.09% C, 0.025% P, 0.029% S, 0.18% V, and the rest is Fe and inevitable impurities) preheated at 880°C for 140 minutes are added along with the molten iron flow. The chemical composition and mass fraction of the molten iron in the ladle are as follows: 19.91% B, 0.26% C, 1.27% Si, 0.38% Al, 0.005% S, 0.083% P, the remainder is Fe and unavoidable impurities), the amount of ferrotitanium particles added accounts for 1.3% of the mass fraction of the molten iron entering the ladle, the amount of ferroboron particles added accounts for 0.36% of the mass fraction of the molten iron entering the ladle, and the size of the ferrotitanium particles and ferroboron particles is 2-4 mm; copper-magnesium alloy (the chemical composition and mass fraction of the copper-magnesium alloy are: 94.5% Cu, 5.5% Mg) and rare earth ferrosilicon alloy (the chemical composition of the rare earth ferrosilicon alloy is: and mass fractions are: 36.90% RE, 45.37% Si, 1.26% Ba, 0.82% Ca, 0.64% Al, 0.16% Ti, 0.27% Mn, the remainder being Fe and unavoidable impurities), the copper-magnesium alloy and rare earth ferrosilicon alloy added account for 0.36% and 0.11% of the mass fraction of the molten iron added to the ladle respectively, and the sizes of the copper-magnesium alloy and the rare earth ferrosilicon alloy are 5-8 mm; after all the molten iron enters the ladle, sprinkle an appropriate amount of heat-insulating slag-aggregating agent into the ladle to cover it, and then skim the slag after calming for 4.5 minutes to obtain high-chromium cast iron molten iron, and pour it into the casting mold on the centrifuge when the temperature drops to 1428°C;

[0038] ② Roller core ductile iron 2 The smelting process of molten iron is to first mix and heat the waste cast iron, waste ductile iron, scrap steel and carburizer in another 1500 kg acid medium frequency induction furnace to melt, add metallic copper after the molten iron is melted, heat the molten iron to above 1450℃, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.27% C, 0.95% Si, 0.46% Cu, 0.08% Ti, 0.36% Mn, 0.21% Cr, 0.04% Ni, 0.03% Mo, 0.064% P, 0.029% S, the rest is Fe and inevitable impurities; the temperature of the molten iron out of the furnace is controlled at 1488°C, and during the molten iron out of the furnace, ferrosilicon particles preheated at 680°C for 100 minutes are added with the molten iron flow (the chemical composition and mass fraction of the ferrosilicon particles are: 75.89% Si, 0.32% A l, 0.17% Ca, 0.26% Mn, 0.33% Cr, 0.029% P, 0.014% S, 0.13% C, the balance is Fe and inevitable impurities), the amount of ferrosilicon particles added accounts for 0.75% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15mm; rare earth magnesium ferrosilicon alloy is pre-added at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 6.94% RE, 7.81% Mg, 40.67% Si, 0.38% Ti, 0.25% Al, the balance is Fe and inevitable impurities), the amount of rare earth magnesium ferrosilicon alloy added accounts for 1.45% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; after the molten iron in the ladle is skimmed and allowed to stand, ductile iron molten iron is obtained, and when the temperature drops to 1322°C, it is poured into a casting mold on a centrifuge;

[0039] ③ The high chromium cast iron molten iron of 1428° C. obtained in step ① is poured into a casting mold rotating at high speed on a vertical centrifuge, and the centrifuge speed is 1000 rpm; the thickness of the high chromium cast iron outer layer 1 is 50 mm; after the outer layer molten iron is poured, "O" type glass slag dried at 160° C. for 2.2 hours is added, and the "O" type glass slag is added in an amount of 1.15 kg (1.15 kg / m2) according to the inner surface area of ​​the high chromium cast iron outer layer 1 per square meter. 2 ) meter; when the outer layer of molten iron was poured for 7 minutes, the centrifuge speed was reduced to 780rpm; the inner surface temperature of the outer layer was measured with a far-infrared thermometer. When the inner surface temperature was 1280-1300°C, the mold speed was reduced to 630rpm, and the ductile iron molten iron at a temperature of 1322°C obtained in step ② was poured; 30 minutes after the ductile iron molten iron was poured, the centrifuge was stopped; after continuing to cool in the mold for 3.5 hours, the roller was removed from the mold;

[0040] ④ The roller is rough-machined after grinding and sand removal. The rough-machined roller is heated to 1000℃ with the furnace, kept warm for 3.2 hours, spray-cooled to a roller surface temperature of 400-430℃, and then heated to 550℃ in the furnace, kept warm for 13 hours, cooled to a temperature below 160℃ in the furnace, and air-cooled to room temperature after being removed from the furnace. Finally, it is fine-machined to the specified size and accuracy to obtain a high-strength and high-toughness high-chromium cast iron roller. The mechanical properties of the roller are shown in Table 1.

[0041] Embodiment 2:

[0042] The high-strength and high-toughness high-chromium cast iron roll is made of a high-chromium cast iron outer layer 1 and a ductile iron roll core 2 by centrifugal composite casting. The specific preparation process steps are:

[0043] ① Two acidic medium frequency induction furnaces are used to melt the outer layer high chromium cast iron 1 and the roller core ductile iron 2 respectively; the smelting process of the high chromium cast iron is: firstly, scrap steel and carburizer are added to a 1000 kg acidic medium frequency induction furnace, and after the molten iron is melted, ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese are added to adjust the composition of the molten iron; then, the molten iron is heated to 1566°C, metallic aluminum and ferrotitanium are added in turn, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at 2.47% C, 18.98% Cr, 0.77% Mo, 0.73% W, 0.67% Si, 1.37% Mn, 0.13% N, 0. .37% Al, 0.35% Ti, 0.033% S, 0.042% P, and the rest is Fe and inevitable impurities; when the temperature of the molten iron in the furnace drops to 1517°C, the molten iron is discharged from the furnace to a ladle, and in the process of the molten iron being discharged from the furnace, titanium iron particles preheated at 850°C for 150 minutes (the chemical composition and mass fraction of the titanium iron particles are: 68.64% Ti, 0.37% Al, 0.08% Si, 0.15% Mn, 0.11% C, 0.027% P, 0.019% S, 0.14% V, and the rest is Fe and inevitable impurities) and ferroboron particles (the ferroboron particles are The chemical composition and mass fraction of the particles are: 19.54% B, 0.29% C, 1.36% Si, 0.41% Al, 0.008% S, 0.093% P, the remainder is Fe and inevitable impurities), the amount of ferrotitanium particles added accounts for 1.2% of the mass fraction of the molten iron entering the ladle, the amount of ferroboron particles added accounts for 0.37% of the mass fraction of the molten iron entering the ladle, and the size of the ferrotitanium particles and ferroboron particles is 2-4 mm; copper-magnesium alloy (the chemical composition and mass fraction of the copper-magnesium alloy are: 94% Cu, 6% Mg) and rare earth ferrosilicon alloy (the chemical composition and mass fraction of the rare earth ferrosilicon alloy are: The composition and mass fraction are: 36.45% RE, 46.50% Si, 1.07% Ba, 0.83% Ca, 1.13% Al, 0.16% Ti, 0.31% Mn, the balance is Fe and inevitable impurities), the copper-magnesium alloy and rare earth ferrosilicon alloy added account for 0.35% and 12% of the mass fraction of the molten iron added to the ladle respectively, and the size of the copper-magnesium alloy and the rare earth ferrosilicon alloy is 5-8 mm; after all the molten iron enters the ladle, sprinkle a proper amount of heat-insulating slag-aggregating agent into the ladle to cover it, and then skim the slag after calming for 4 minutes to obtain high-chromium cast iron molten iron, and pour it into a casting mold on a centrifuge when the temperature drops to 1426°C;

[0044] ② Roller core ductile iron 2 The smelting process of molten iron is to first mix and heat the waste cast iron, waste ductile iron, scrap steel and carburizer in another 3000 kg acid medium frequency induction furnace to melt, add metallic copper after the molten iron is melted, heat the molten iron to above 1450℃, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.13% C, 1.07% Si, 0.41% Cu, 0.09% Ti , 0.32% Mn, 0.13% Cr, 0.08% Ni, 0.11% Mo, 0.056% P, 0.031% S, the rest is Fe and inevitable impurities; the temperature of the molten iron out of the furnace is controlled at 1482°C, and in the process of the molten iron out of the furnace, ferrosilicon particles preheated at 650°C for 110 minutes are added with the molten iron flow (the chemical composition and mass fraction of the ferrosilicon particles are: 74.82% Si, 0.62% Al, 0.37% Ca, 0.18% Mn, 0.26% Cr, 0.035% P, 0.014% S, 0.15% C, the balance is Fe and inevitable impurities), the amount of ferrosilicon particles added accounts for 0.7% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15mm; rare earth magnesium ferrosilicon alloy is pre-added at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 6.36% RE, 8.68% Mg, 38.17% Si, 0.38% Ti, 0.53% Al, the balance is Fe and inevitable impurities), the amount of rare earth magnesium ferrosilicon alloy added accounts for 1.50% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; after the molten iron in the ladle is skimmed and allowed to stand, ductile iron molten iron is obtained, and when the temperature drops to 1318°C, it is poured into a casting mold on a centrifuge;

[0045] ③ The high chromium cast iron molten iron of 1426° C. obtained in step ① is poured into a casting mold rotating at high speed on a vertical centrifuge, and the centrifuge speed is 950 rpm; the thickness of the high chromium cast iron outer layer 1 is 40 mm; after the outer layer molten iron is poured, "O" type glass slag dried at 150° C. for 2.5 hours is added, and the amount of "O" type glass slag is added according to the inner surface area of ​​the high chromium cast iron outer layer 1 per square meter (1.1 kg / m 2 ) meter; when the outer layer of molten iron was poured for 6 minutes, the centrifuge speed was reduced to 800rpm; the inner surface temperature of the outer layer was measured with a far-infrared thermometer. When the inner surface temperature was 1280-1300°C, the mold speed was reduced to 600rpm, and the ductile iron molten iron at a temperature of 1318°C obtained in step ② was poured; 28 minutes after the ductile iron molten iron was poured, the centrifuge was stopped; after continuing to cool in the mold for 4 hours, the roller was removed from the mold;

[0046] ④ The roller is rough-machined after grinding and sand removal. The rough-machined roller is heated to 980℃ with the furnace, kept warm for 3.5 hours, spray-cooled to a roller surface temperature of 380-410℃, and then heated to 530℃ in the furnace, kept warm for 14 hours, cooled to a temperature below 160℃ in the furnace, and air-cooled to room temperature after being removed from the furnace. Finally, it is fine-machined to the specified size and accuracy to obtain a high-strength and high-toughness high-chromium cast iron roller. The mechanical properties of the roller are shown in Table 1.

[0047] Embodiment 3:

[0048] The high-strength and high-toughness high-chromium cast iron roll is made of a high-chromium cast iron outer layer 1 and a ductile iron roll core 2 by centrifugal composite casting. The specific preparation process steps are:

[0049] ① Two acidic medium frequency induction furnaces are used to melt the outer layer high chromium cast iron 1 and the roller core ductile iron 2 respectively; the smelting process of the high chromium cast iron is: firstly, scrap steel and carburizer are added to a 1500 kg acidic medium frequency induction furnace, and after the molten iron is melted, ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese are added to adjust the composition of the molten iron; then, the molten iron is heated to 1579°C, metallic aluminum and ferrotitanium are added in turn, and the chemical composition and mass fraction of the molten iron in the furnace are controlled at 2.63% C, 18.65% Cr, 0.94% Mo, 0.58% W, 0.86% Si, 1.24% Mn, 0.17% N, 0. .32% Al, 0.44% Ti, 0.036% S, 0.040% P, and the rest is Fe and inevitable impurities; when the temperature of the molten iron in the furnace drops to 1532°C, the molten iron is discharged from the furnace to a ladle, and in the process of the molten iron being discharged from the furnace, titanium iron particles (the chemical composition and mass fraction of the titanium iron particles are: 71.28% Ti, 0.27% Al, 0.06% Si, 0.16% Mn, 0.11% C, 0.028% P, 0.025% S, 0.19% V, and the rest is Fe and inevitable impurities) and ferroboron particles (the ferroboron particles) preheated at 900°C for 120 minutes are added with the molten iron flow The chemical composition and mass fraction of the particles are: 20.76% B, 0.27% C, 1.39% Si, 0.22% Al, 0.003% S, 0.076% P, the balance is Fe and inevitable impurities), the amount of ferrotitanium particles added accounts for 1.4% of the mass fraction of the molten iron entering the ladle, the amount of ferroboron particles added accounts for 0.35% of the mass fraction of the molten iron entering the ladle, and the size of the ferrotitanium particles and ferroboron particles is 2-4 mm; copper-magnesium alloy (the chemical composition and mass fraction of the copper-magnesium alloy are: 95% Cu, 5% Mg) and rare earth ferrosilicon alloy (the chemical composition of the rare earth ferrosilicon alloy is: The composition and mass fraction are: 37.81% RE, 44.06% Si, 1.17% Ba, 1.33% Ca, 1.08% Al, 0.14% Ti, 0.38% Mn, and the balance is Fe and inevitable impurities), the copper-magnesium alloy and rare earth ferrosilicon alloy added account for 0.38% and 0.10% of the mass fraction of the molten iron added to the ladle respectively, and the size of the copper-magnesium alloy and the rare earth ferrosilicon alloy is 5-8mm; after all the molten iron enters the ladle, sprinkle a proper amount of heat-insulating slag-aggregating agent into the ladle to cover it, and then skim the slag after calming for 5 minutes to obtain high-chromium cast iron molten iron, and pour it into the casting mold on the centrifuge when the temperature drops to 1433℃;

[0050] ② Roller core ductile iron 2 The smelting process of molten iron is to first mix and heat the waste cast iron, waste ductile iron, scrap steel and carburizer in another 3000 kg acid medium frequency induction furnace to melt, add metallic copper after the molten iron is melted, heat the molten iron to above 1450℃, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.38% C, 0.91% Si, 0.48% Cu, 0.05% Ti , 0.49% Mn, 0.18% Cr, 0.14% Ni, 0.15% Mo, 0.059% P, 0.031% S, the rest is Fe and inevitable impurities; the temperature of the molten iron out of the furnace is controlled at 1497°C, and in the process of the molten iron out of the furnace, ferrosilicon particles preheated at 720°C for 90 minutes are added with the molten iron flow (the chemical composition and mass fraction of the ferrosilicon particles are: 76.17% Si, 0.64% A l, 0.52%Ca, 0.41%Mn, 0.26%Cr, 0.035%P, 0.011%S, 0.16%C, the balance is Fe and inevitable impurities), the amount of ferrosilicon particles added accounts for 0.8% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15mm; rare earth magnesium ferrosilicon alloy is pre-added at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 7.81%RE, 7.24%Mg, 42.05%Si, 0.37%Ti, 0.52%Al, the balance is Fe and inevitable impurities), the amount of rare earth magnesium ferrosilicon alloy added accounts for 1.50% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; after the molten iron in the ladle is skimmed and allowed to stand, ductile iron molten iron is obtained, and when the temperature drops to 1327°C, it is poured into a casting mold on a centrifuge;

[0051] ③ The high chromium cast iron molten iron of 1433° C. obtained in step ① is poured into a casting mold rotating at high speed on a vertical centrifuge, and the centrifuge speed is 1050 rpm; the thickness of the high chromium cast iron outer layer 1 is 60 mm; after the outer layer molten iron is poured, "O" type glass slag dried at 180° C. for 2.0 hours is added, and the amount of "O" type glass slag is added according to the inner surface area of ​​the high chromium cast iron outer layer 1 per square meter (1.2 kg / m 2 ) meter; when the outer layer of molten iron was poured for 8 minutes, the centrifuge speed was reduced to 750rpm; the inner surface temperature of the outer layer was measured with a far-infrared thermometer. When the inner surface temperature was 1280-1300°C, the mold speed was reduced to 650rpm, and the ductile iron molten iron at a temperature of 1327°C obtained in step ② was poured; 32 minutes after the ductile iron molten iron was poured, the centrifuge was stopped; after continuing to cool in the mold for 3 hours, the roller was removed from the mold;

[0052] ④ The roller is rough-machined after grinding and sand removal. The rough-machined roller is heated to 1010℃ with the furnace, kept warm for 3 hours, spray-cooled to a roller surface temperature of 420-450℃, and then heated to 560℃ in the furnace, kept warm for 12 hours, cooled to a temperature below 160℃ in the furnace, and air-cooled to room temperature after being removed from the furnace. Finally, it is fine-machined to the specified size and accuracy to obtain a high-strength and high-toughness high-chromium cast iron roller. The mechanical properties of the roller are shown in Table 1.

[0053] Table 1 Mechanical properties of high strength and toughness high chromium cast iron rolls

[0054]

[0055] The invention effectively improves the mechanical properties of the roller by adjusting the composition ratio of the roller and adopting a composite layer structure. The hardness of the outer layer of the roller is greater than 82HSD, the tensile strength is greater than 830MPa, and the impact toughness is greater than 10J / cm 2 , the tensile strength of the roller core is greater than 650MPa, and the elongation is greater than 8%. The high chromium cast iron of the outer layer of the roller of the present invention and the ductile iron of the roller core achieve good metallurgical bonding, and the thickness of the transition layer can be controlled within 5-8mm, ensuring that the roller is firmly bonded; the chromium content of the roller core is low, ensuring that the ductile iron of the roller core has high strength and high toughness. The roller of the present invention has high hardness, good hardness uniformity, excellent wear resistance and good thermal fatigue resistance. When used in the cutting frame of the rod and wire rolling mill, its service life is increased by 70-90% compared with the traditional bainite ductile iron roller, and the production cost is reduced by more than 20% compared with the traditional bainite ductile iron roller. The high chromium cast iron roller of the present invention can improve the strength, toughness and wear resistance of the roller, can increase its service life, and can also reduce the cost of the roller. The use of the roller of the present invention can significantly improve the operation rate of the steel rolling mill, reduce the labor intensity of workers, reduce the production cost of rolled materials, improve the surface quality of rolled materials, and has good economic and social benefits in promotion and application.

Claims

1. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll, characterized in that: The high-strength and high-toughness high-chromium cast iron roll is made by centrifugally composite casting of a high-chromium cast iron outer layer and a ductile iron roll core, and the specific preparation process steps include the following: ① Two acidic medium frequency induction furnaces are used to melt the outer layer high chromium cast iron and the roller core ductile iron respectively; the smelting process of high chromium cast iron is: first add scrap steel and carburizer into the acidic medium frequency induction furnace, and then add ferrochrome, ferrochrome nitride, ferromolybdenum, ferrotungsten, ferrosilicon and ferromanganese to adjust the composition of the molten iron after the molten iron is melted; then heat the molten iron to 1566-1579℃, add metal aluminum and ferrotitanium in turn, and control the chemical composition and mass fraction of the molten iron in the furnace to 2.47 -2.63% C, 18.65-18.98% Cr, 0.77-0.94% Mo, 0.58-0.73% W, 0.67-0.86% Si, 1.24-1.37% Mn, 0.13-0.17% N, 0.32-0.37% Al, 0.35-0.44% Ti, <0.040% S, <0.045% P, the rest is Fe and unavoidable impurities; when the temperature of the molten iron in the furnace drops to 15 At 17-1532℃, the molten iron is discharged from the furnace to the ladle, and during the molten iron discharge process, titanium iron particles and ferroboron particles preheated at 850-900℃ for 120-150 minutes are added with the molten iron flow, the amount of titanium iron particles added accounts for 1.2-1.4% of the mass fraction of the molten iron entering the ladle, and the amount of ferroboron particles added accounts for 0.35-0.37% of the mass fraction of the molten iron entering the ladle. The size of the titanium iron particles and ferroboron particles is 2-4mm; The copper-magnesium alloy and the rare earth ferrosilicon alloy are added in an amount of 0.35-0.38% and 0.10-12% of the mass fraction of the molten iron added to the ladle, respectively, and the size of the copper-magnesium alloy and the rare earth ferrosilicon alloy is 5-8 mm; after all the molten iron enters the ladle, a proper amount of heat-insulating slag-aggregating agent is sprinkled into the ladle to cover it, and the slag is removed after calming for 4-5 minutes to obtain high-chromium cast iron molten iron, and when the temperature drops to 1426-1433°C, it is poured into a casting mold on a centrifuge; ② The smelting process of roller core ductile iron molten iron is to first mix and heat the waste cast iron, waste ductile iron, scrap steel and carburizer in another acidic medium frequency induction furnace to melt, add metallic copper after the molten iron is melted, heat the molten iron to above 1450℃, add ferrosilicon, ferromanganese and ferrotitanium, and control the chemical composition and mass fraction of the molten iron in the furnace to 3.13-3.38% C, 0.91-1.07% Si, 0.41-0.48% Cu, 0.05-0.09% Ti, 0.32-0.49% Mn, <0.25% Cr, ≤0.20% Ni, ≤0.20% Mo, ≤0.070% P, ≤0.035% S, the rest is Fe and unavoidable impurities; the temperature of the molten iron out of the furnace is controlled at 1482-1497°C, and in the process of the molten iron out of the furnace, ferrosilicon particles preheated at 650-720°C for 90-110 minutes are added with the molten iron flow, the amount of ferrosilicon particles added accounts for 0.7-0.8% of the mass fraction of the molten iron entering the ladle, and the size of the ferrosilicon particles is 6-15mm; rare earth magnesium ferrosilicon alloy is pre-added at the bottom of the ladle, the amount of rare earth magnesium ferrosilicon alloy added accounts for 1.40-1.50% of the mass fraction of the molten iron entering the ladle; the size of the rare earth magnesium ferrosilicon alloy is 6-12mm; the molten iron in the ladle is skimmed and allowed to stand to obtain ductile iron molten iron, and when the temperature drops to 1318-1327°C, it is poured into the mold on the centrifuge; ③ The high chromium cast iron molten iron at a temperature of 1426-1433° C. obtained in step ① is poured into a casting mold rotating at high speed on a vertical centrifuge, and the centrifuge speed is 950-1050 rpm; the thickness of the outer layer of the high chromium cast iron is 40-60 mm; after the outer layer of molten iron is poured, "O" type glass slag dried at 150-180° C. for 2.0-2.5 hours is added, and the "O" type glass slag is added in an amount of 1.1-1.2 kg (i.e., 1.1-1.2 kg / m 2 ) meter; when the outer layer of molten iron is poured for 6-8 minutes, the centrifuge speed is reduced to 750-800rpm; the inner surface temperature of the outer layer is measured with a far-infrared thermometer. When the inner surface temperature is 1280-1300°C, the mold speed is reduced to 600-650rpm, and the ductile iron molten iron of 1318-1327°C obtained in step ② is poured; 28-32 minutes after the ductile iron molten iron is poured, the centrifuge is stopped; after continuing to cool in the mold for 3-4 hours, the roller is removed from the mold; ④ The rollers are roughly processed after grinding and sand cleaning. The rough-processed rollers are heated to 980-1010℃ with the furnace, kept warm for 3-3.5 hours, spray-cooled to the roller surface temperature of 380-450℃ after being taken out of the furnace, and then heated to 530-560℃ in the furnace, kept warm for 12-14 hours, cooled in the furnace to a temperature below 160℃, air-cooled to room temperature after being taken out of the furnace, and finally fine-processed to the specified size and precision to obtain high-strength and high-toughness high-chromium cast iron rollers.

2. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of the titanium-iron particles are: 68.64-71.28% Ti, <0.5% Al, <0.10% Si, <0.20% Mn, <0.20% C, <0.03% P, <0.03% S, <0.50% V, and the remainder is Fe and unavoidable impurities.

3. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of the ferroboron particles are: 19.54-20.76% B, ≤0.5% C, ≤2% Si, ≤0.5% Al, ≤0.01% S, ≤0.1% P, and the remainder is Fe and unavoidable impurities.

4. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of the copper-magnesium alloy are: 94-95% Cu, 5-6% Mg, and the sum of the two is 100%.

5. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of rare earth ferrosilicon alloy are: 36.45-37.81% RE, 44.06-46.50% Si, <2.0% Ba, <2.0% Ca, <1.5% Al, <0.3% Ti, <0.5% Mn, and the remainder is Fe and unavoidable impurities.

6. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of the ferrosilicon particles are: 74.82-76.17% Si, ≤1.0% Al, ≤1.0% Ca, ≤0.5% Mn, ≤0.5% Cr, ≤0.04% P, ≤0.02% S, ≤0.20% C, and the remainder is Fe and unavoidable impurities.

7. A method for manufacturing a high-strength and high-toughness high-chromium cast iron roll according to claim 1, characterized in that: As mentioned above, the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 6.36-7.81% RE, 7.24-8.68% Mg, 38.17-42.05% Si, ≤1% Ti, ≤1% Al, and the remainder is Fe and unavoidable impurities.

8. A high-strength and high-toughness high-chromium cast iron roll prepared according to the method described in any one of claims 1 to 7.